2019
DOI: 10.1089/jamp.2018.1457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nebulizer Location and Spontaneous Breathing on Aerosol Delivery During Airway Pressure Release Ventilation in Bench Testing

Abstract: Spontaneous breathing increased the albuterol delivery during APRV, compared with APRV alone and PCV modes. Placing the nebulizer proximal to the ventilator was more efficient for all modes tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The only significant difference is between the JN-H (0.47 ± 0.06 %/min) and the VMN-L ( P = 0.015). Previous studies have reported that the %/min of albuterol delivered by a JN was 0.52 %/min, whereas the delivery by a VMN was 2.14 %/min [23,24]. The delivery efficiency of the JN was comparable to our data; however, the delivery efficiency of the VMN-L in our study with colistin is 0.81 ± 0.20 %/min lower than that with salbutamol, as found by previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The only significant difference is between the JN-H (0.47 ± 0.06 %/min) and the VMN-L ( P = 0.015). Previous studies have reported that the %/min of albuterol delivered by a JN was 0.52 %/min, whereas the delivery by a VMN was 2.14 %/min [23,24]. The delivery efficiency of the JN was comparable to our data; however, the delivery efficiency of the VMN-L in our study with colistin is 0.81 ± 0.20 %/min lower than that with salbutamol, as found by previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 5.8% respondents reported the need to increase sedation in order to improve ventilator-patient synchronization. Previous studies have shown that ventilation mode, breathing parameters, heat and humidity, gas density, and artificial airways influence aerosol delivery to critically ill subjects[12,14,30]. About 40.8% respondents reported never changing the ventilator settings during aerosol therapy; this included 33.9% and 20.8% of those who use the jet nebulizer and vibrating mesh nebulizer, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a lung model, VT delivery during APRV was lower when compared to other modes (122). Spontaneous breathing during APRV results in variable VT and carries a risk of high VT delivery (123), yet aerosol deposition is increased compared to other modes (124). When compared to BiPAP with similar settings, APRV resulted in higher mPaw and higher total PEEP, and PEEP could not be predicted by lung mechanics (125).…”
Section: Bench Modelsmentioning
confidence: 93%